THE FORMULATION OF MINIMUM WAGE (MW) IN THE LIGHT OF MAQASHID AL-SHARIA: INDONESIAN CASE - Yulizar D Sanrego (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2017)
Minimum Wage (MW) is a policy set by the government as a basis reference at labor market for every company to pay their workers wages. Since workers always have a low bargaining position when dealing with employers in the determination of their wage rates, therefore the MW could becomes the safety net for workers to have